What Drives the Relationship Between Early Criminal Involvement and School Dropout? - Rud, Iryna (Journal of quantitative criminology, 2018)
We examine the relationship between early criminal involvement and school dropout, and analyze which factors underlie this relationship, making use of administrative data from the Netherlands.